Numerical and experimental analysis on the helicopter rotor dynamic load controlled by the actively trailing edge flap. (8th February 2022) - Zhou, Z X; Huang, X C; Tian, J J; Hua, H X; Tang, M; Wang, C
Abstract: Reducing the rotor dynamic load is an important issue to improve the performance and reliability of a helicopter. The control mechanism of the actively controlled flap (ACF) on the rotor dynamic load is numerically and experimentally investigated by a 3-blade helicopter rotor in this paper. In the aero-elastic numerical approach, the complex motion of the rotor such as the stretching, bending, torsion and pitching of the blade including the deflection of the ACF are all taken into consideration in the structural formulation. The aerodynamic solution adopted the vortex lattice method combined with the free wake model, in which the influence of ACF on the free wake and the aerodynamic load on the blade is taken into account as well. While the experimental method of measuring hub loads and acoustic was accomplished by a rotor rig in a wind tunnel. The result shows that the 3/rev ACF actuation can reduce the 3 ω hub load by more than 50% at maximum, which is significantly better than the 4/rev control. While 4/rev has greater potential to reduce blade vortex interaction (BVI) loads than 3/rev with µ  = 0.15. Further mechanistic analysis shows that by changing the phase difference between the dynamic load on the flap and the rest of the blade, the peak load on the whole blade can be improved, thus achieving effective control of the hub dynamic load, the flap reaches the minimum angle of attack at 90 ∘ –100 ∘ azimuth under best control condition; when the BVI load is perfectly controlled, the flap reaches the minimum angle of attack at 140 ∘ azimuth, and by changing the circulation of the wake, the intensity of BVI in the advancing side is improved. Moreover, an interesting finding in the optimal control of noise and vibration is that an overlap point exists on the motion patterns of the flap with different frequencies.